A new classification and its value evaluation for intermediate column fractures of the distal radius - Ying Yang (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Intermediate column fractures of the distal radius (ICF) are fractures only or mainly limited to the lunate fossa of the distal radius. There are no classification systems and its value evaluation for ICF in the literature. Methods According to the characteristics of ICF, ICF were divided into the volar, dorsal, split, collapse, and collapse with split types. Inter- and intra-observer agreements were analyzed with kappa statistics. Seventy-four patients with ICF were retrospectively studied from January 2008 to June 2016. Surgical approach and reduction-fixation method were taken under the guidelines of the classification in 54 patients with displaced fractures, while conservative treatment was taken in 16 patients with non-obvious displaced fractures and 4 patients with displaced fractures who declined surgery. Results The inter- and intra-observer kappa coefficients were 0.875~0.925 and 0.900~0.950, respectively. All patients were followed up for 13~36 months (average, 18.4 months). At the last follow-up, according to Gartland and Werley score of the functional recovery of wrist, all except 3 patients had excellent or good results (the excellent and good rate was 95.95%). Conclusion The classification reflects the characteristics of ICF and may provide an important reference for choosing treatment and evaluating prognosis.